(untitled) (Clinics, 2012)
OBJECTIVE: Experimental studies on lung preservation have always been performed using animal models. We present ex vivo lung perfusion as a new model for the study of lung preservation. Using human lungs instead of animal models may bring the results of experimental studies closer to what could be expected in clinical practice. METHOD: Brain-dead donors whose lungs had been declined by transplantation teams were used. The cases were randomized into two groups. In Group 1, Perfadex®was used for pulmonary preservation, and in Group 2, LPDnac, a solution manufactured in Brazil, was used. An ex vivo lung perfusion system was used, and the lungs were ventilated and perfused after 10 hours of cold ischemia. The extent of ischemic-reperfusion injury was measured using functional and histological parameters. RESULTS: After reperfusion, the mean oxygenation capacity was 405.3 mmHg in Group 1 and 406.0 mmHg in Group 2 (p = 0.98). The mean pulmonary vascular resistance values were 697.6 and 378.3 dyn·s·cm-5, respectively (p =0.035). The mean pulmonary compliance was 46.8 cm H20 in Group 1 and 49.3 ml/cm H20 in Group 2 (p =0.816). The mean wet/dry weight ratios were 2.06 and 2.02, respectively (p=0.87). The mean Lung Injury Scores for the biopsy performed after reperfusion were 4.37 and 4.37 in Groups 1 and 2, respectively (p = 1.0), and the apoptotic cell counts were 118.75/mm² and 137.50/mm², respectively (p=0.71). CONCLUSION: The locally produced preservation solution proved to be as good as Perfadex®. The clinical use of LPDnac may reduce costs in our centers. Therefore, it is important to develop new models to study lung preservation.